Method for purifying serine protease recovered from a fruit source - Ling, Tau Chuan; Amid, Mehrnoush; Tan, Chin Ping; Mirhosseini, Hamed; Ab. Aziz, Norashikin (2011)
A method for purifying proteases from a crude feedstock including the steps of providing a heating treatment to said crude feedstock at a plurality of time periods to produce a heat-treated feedstock in an aqueous two-phase system (ATPS), determining a proteolytic activity and a protein concentration of the heat-treated feedstock, and recovering the protease from the heat-treated feedstock. The crude feedstock includes a source of fruit from which the proteases are recovered.